Occupational Physicians’ Management of Workers With Multiple Sclerosis in Italy: Results From a Survey - Rondinone, Bruna Maria; Buresti, Giuliana; Iavicoli, Sergio; Durando, Paolo; Battaglia, Mario Alberto; Dini, Guglielmo; Montecucco, Alfredo; Rahmani, Alborz; Debarbieri, Nicoletta; Bandiera, Paolo; Ponzio, Michela; Manacorda, Tommaso; et al. (La Medicina del Lavoro, 2024)
Background: This study, conducted on a sample of Italian occupational physicians (OPs), aimed to gather data regarding professional activity and their needs in managing workers with multiple sclerosis. Methods: A convenience sample of OPs recruited by e-mail invitation to the list of Italian Society of Occupational Medicine members was considered. A total of 220 OPs participated between July and October 2022. An ad hoc questionnaire was developed based on previous survey experiences. It investigated, among others, the characteristics of OP respondents, the evaluation of fitness for work issues, and the OP training and updating needs on multiple sclerosis and work. Results: Ninety-one percent of OPs had to assess the fitness for work of workers with multiple sclerosis during their activity. Sixty-four percent experienced particular difficulties in issuing a fitness for work judgment. Regarding the level of knowledge on multiple sclerosis, 54% judged it sufficient. The “Assessment of fitness for work for the specific task” and the “Role of the OPs in identifying reasonable accommodations” were the most interesting training topics regarding MS management in work contexts chosen by the respondents. Conclusions:The interest in the work inclusion and job retention of people with disability, particularly the aspects linked to the Identification and implementation of reasonable accommodations, will require integration with the occupational safety and health protection system and will undoubtedly impact the OP’s activities.